2023
DOI: 10.1101/2023.09.27.559859
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reconstitution of Early Paclitaxel Biosynthetic Network

Jack Chun-Ting Liu,
Ricardo De La Pena,
Christian Tocol
et al.

Abstract: Paclitaxel is an anticancer therapeutic produced by the yew tree. Over the last two decades, a significant bottleneck in the reconstitution of early paclitaxel biosynthesis has been the propensity of heterologously expressed pathway cytochromes P450, including taxadiene 5α-hydroxylase (T5αH), to form multiple products. This diverts metabolic flux away from the paclitaxel precursor, taxadien-5α-ol, thus previous attempts of reconstitution have not yielded sufficient material for characterization, regardless of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…The discovery also highlights that catalytic promiscuity is somewhat common in the cytochrome P450s and acyltransferases of baccatin III biosynthesis. Previous studies have demonstrated that T5aH can catalyze the formation of many unknown oxygenated products other than taxadien-5a-ol (59)(60)(61), and recently it was revealed that this enzyme even has weak cyclase activity leading to the oxetane structure (62), which indicates its functional promiscuity. T13aH could catalyze C13 hydroxylation with taxadien-5a-ol and taxadien-5a-yl acetate as substrates, thereby exhibiting a substrate flexibility similar to that of cytochrome P450s in paclitaxel biosynthesis (24).…”
Section: Discussionmentioning
confidence: 99%
“…The discovery also highlights that catalytic promiscuity is somewhat common in the cytochrome P450s and acyltransferases of baccatin III biosynthesis. Previous studies have demonstrated that T5aH can catalyze the formation of many unknown oxygenated products other than taxadien-5a-ol (59)(60)(61), and recently it was revealed that this enzyme even has weak cyclase activity leading to the oxetane structure (62), which indicates its functional promiscuity. T13aH could catalyze C13 hydroxylation with taxadien-5a-ol and taxadien-5a-yl acetate as substrates, thereby exhibiting a substrate flexibility similar to that of cytochrome P450s in paclitaxel biosynthesis (24).…”
Section: Discussionmentioning
confidence: 99%